HUBUNGAN DUKUNGAN SOSIAL TERHADAP STRES DALAM PENYUSUNAN TUGAS AKHIR MAHASISWA - Annisa Primita Nurfadila; Andhita Dyorita Khoiryasdien (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This research is motivated by the high psychological burden of final year students when completing their thesis, where social support is assumed to be a crucial element in reducing stress. The main focus of this study is to analyze the relationship between social support as an independent variable and stress levels as a dependent variable. Using a quantitative method with a descriptive correlational design, the study involved 100 students selected through a purposive sampling technique. The data collection instrument was a Likert scale questionnaire that met the criteria for high validity and reliability, with a Cronbach's Alpha value of 0.948 for social support and 0.753 for stress. The data were then processed through a Pearson Product Moment correlation test using SPSS software. The results of the statistical analysis revealed a correlation coefficient value of r = -0.092 with a significance level of p = 0.365 (p > 0.05). This empirical finding indicates that there is no significant relationship between social support and stress levels in respondents. The main conclusion of the study confirms that stress in final year students is not predominantly determined by external social support, but rather is more influenced by individual internal factors such as coping mechanisms, cognitive perceptions, and independent adaptation abilities. This research contributes to the development of more holistic stress management by emphasizing strengthening students' internal resilience in facing academic challenges to ensure the successful completion of their final assignments.